Pendampingan Pengolahan Data Penelitian dengan Aplikasi SPSS Bagi Mahasiswa - Ulum, Miftachul; Mun'im, Abdul; Zawawi, Abdullah; Al Maghfuri, Rahmah Salsabila (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service activity aims to provide understanding and training in using the SPSS application in statistical data processing. This activity was attended by 12 students of the Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya on November 14, 2024 through the Google Meet application. The mentoring activity was carried out through stages, preliminary stage, implementation stage and evaluation stage. The results of the mentoring were obtained by participants being able to understand and practice the application in statistical data processing activities. Participants were also able to prepare the application starting from installation to use.